Устойчивость слоистых материалов при отсутствии деформаций в плоскости слоев - Чехов, В.Н. (Прикладная механика, 2010)
The stability of equilibrium state of layered bodies is studied for biaxial loading.
It is assumed that deformation is absent in the layer plane. The three-dimensional linearized
theory of stability jointly with the model of piece-wise bodies are used. Two models
of layered bodies are considered. A solution of concrete problems for layered bodies of different
structure is obtained. The critical values of waveformation parameters and loads corresponding
the loss stability of layered bodies are found. Досліджено стійкість стану рівноваги шаруватих тіл при двовісному навантаженні.
Прийнято гіпотезу про відсутність деформацій в площині шарів. Використано тривимірну лінеарізовану теорію стійкості у поєднанні із моделлю кусково-однорідних тіл. Розглянуто дві моделі шаруватих тіл. Отримано розв’язок конкретних задач для шаруватих тіл різної структури. Визначено критичні значення параметрів навантаження та хвилеутворення, які обумовлюють явище втрати стійкості
шаруватих тіл.